Communicating decisions with a multilingual patient population - Roberts, Celia (Cahiers du Centre de Linguistique et des Sciences du Langage, 2022)
THE NOTION OF ‘LINGUISTIC BARRIERS’ in medical settings usually refers to the use (and possible abuse) of interpreters. However, the language and cultural diversity of patient populations in an increasingly globalised world leads to many encounters where a common language or lingua franca is used. The use of an interpreter is not necessarily a possible option nor indeed may it be the preferred one. Many patients bring to the consultation some fluency in the dominant language of the country in which they are now resident and both patient and doctor may choose to carry out the consultation as a dyadic interaction without the mediation of an interpreter. The decision whether to use an interpreter or not is more complex than many systems allow for. It is often not a simple matter of being able to ‘speak the language’ or not. Everyone is on a continuum of linguistic/ cultural competence and so the conditions for negotiating shared understanding (Gumperz, 1982) can be elusive.